First experiments to determine snow density from diffuse near-infrared transmittance - Gergely, Mathias; Schneebeli, Martin; Roth, Kurt (Cold regions science and technology, 2010)
Snow density is one of the key properties to characterize a snow cover. We present diffuse near-infrared transmittance measurements with an integrating sphere setup in the laboratory. We analyze 8 snow samples taken from melt forms, decomposed, rounded, faceted and machine made snow. Reference measurements of specific surface area (optically equivalent grain size) and density are done by micro-computed tomography and used as input for transmittance calculations. A diffuse flux extinction model cannot be applied to simulate transmittance as our setup cannot be approximated by an infinite snow block thickness. Calculations with a more intricate radiative transfer model (DISORT) agree with our measurements within the estimated grain size and density variability for all probed natural snow types. Only our machine made snow shows a morphology which cannot be modeled by DISORT. Thus, our results show for the first time a direct experimental correlation between transmittance and snow specific surface area and density without the need for an empirical fitting parameter. We feel this to be an important step towards a possible high-resolution, quantitative optical measurement method to determine snow density in combination with an independent specific surface area measurement.